A narrative research of experiences of STEM teachers pursuing doctoral degree - John Nathaniel F. Abrigo; Alyhana Ashleigh A. Abrogena; Daedan Ryu E. Alcantara; Niela Alena V. De Gracia; Allissa C. Juliano; Zohail I. Ador (Journal of Social, Humanity, and Education, 2024)
Purpose: The main purpose of this study is to explore the experiences, struggles, and coping mechanisms of educators currently pursuing doctoral degrees. Research methodology: This narrative research explored the experiences of three (3) STEM teachers in the Division of San Pablo City, who are also enrolled as doctoral students in a private graduate school. Participants were selected through purposive sampling and underwent one-on-one in-person interviews. To better understand STEM-aligned teachers' experiences in teaching vis-à-vis their doctoral education, the Colaizzi method of analysis was utilized. Results: Five themes emerged in this study: (1) practical reasons such as promotion and higher salary cause participants to take doctoral education; (2) challenges such as expensive education, heavy workload, distress, struggles, and strictness of professors are experienced by doctoral students; (3) intrapersonal motivation fuels participants in learning and teaching; (4) cultivating professionally; and (5) personally are what the participants see as benefits of pursuing doctoral education. Limitations: The programs of the participants in their doctoral education were not explicitly specified. Findings may be different if participants take a degree related to their specialization (e.g., science education, mathematics, etc.). In addition, the experiences of teachers teaching in private schools who are pursuing doctoral education may also be explored for comparison of experiences. Contribution: This research could be beneficial to educational institutions where doctoral students teach by adapting to more open policies and regulations that can help teachers attend schools. Moreover, graduate schools may mandate working-student-friendly schedules and policies regarding deadlines and tasks.